IMPLEMENTASI MERIT SYSTEM PADA PEMBINAAN PERSONEL GUNA MENINGKATKAN PROFESIONALISME PRAJURIT TNI AU - Sonny Ariefianto; Afrizal Hendra; Marsono Marsono; Achmad Abdul Lathif (Bajang Institute, 2026)
This study aims to develop a relevant and sustainable performance-based personnel development model within the Indonesian Air Force to enhance soldier professionalism. The research method uses a comparative qualitative approach with data collection techniques thru document analysis of the researcher's field research results from five Indonesian Air Force units that have implemented a performance-based evaluation system, compared with several similar studies. The research results indicate that the implementation of performance-based coaching significantly improves soldier professionalism. This finding is supported by comparative studies showing that units with structured performance evaluation systems have an operational readiness rate 30% higher than conventional units. This research contributes to the development of a meritocracy-based military human resource management model with practical recommendations for integrating performance tracking technology and strengthening the capacity of performance appraisers. The research results show that performance-based personnel development is effective in improving the professionalism of Indonesian Air Force personnel and is suitable to be used as a national model for military human resource development